ANALISIS PEMBENTUKAN KERAK DI DALAM PIPA PDAM SEMARANG - Titis Septianna Sari; Athanasius Priharyoto Bayuseno (JURNAL TEKNIK MESIN, 2015)
Pipes are important components  in a system drinking water to transport water flow. If one of the pipes experiences corrode and scaling, the potential economic losses will be high. To determine the scale formation and corrosion in the pipeline of PDAM Semarang tests was performed including: Chemical Composition Test, Hardness Test, Piping Material Microstructure, SEM-EDX Test and Test XRD. The test results show that the pipe of PDAM Semarang can be classifield as the low carbon steel according to material type "JIS G4051 Type S 09 K". The hardness test results show that the hardness value of the corroded pipe is greater than the hardness value of the new pipeline.From the test results show the chemical composition of pipe PDAM Semarang including low carbon steel with material type "JIS G4051 Type S 09 K". For the hardness test results show that the hardness value of corroded pipe is greater than the hardness value of the new pipeline. Based on the results of EDX (Energy Dispersive X-ray Spectrosopy), element of manganese (Mn) influenced  the composition of the pipe water is 0.483 Mg / l. From XRD (X-ray Diffraction), there are two phases, namely: phase birnesite syn (MnO2) and phase hydroheate rolite (Zn2Mn4 + 3O8.H2O). The results of the two phases can exhibit high levels of Mn and Zn in the water provided  formation of oxide scale on the walls of the pipe.